The androgen clock is an epigenetic predictor of long-term male hormone exposure - Victoria J. Sugrue; Melanie Prescott; Kelly A. Glendining; Donna M. Bond; Steve Horvath; Greg M. Anderson; Michael Garratt; Rebecca E. Campbell; Timothy A. Hore (Proceedings of the National Academy of Sciences, 2025)
Aging is a complex process characterized by biological decline and a wide range of molecular alterations to cells, including changes to DNA methylation. In this study, we used a male-specific epigenetic marker of aging to build an epigenetic predictor that measures long-term androgen exposure in sheep and mice (median absolute error of 4.3 and 1.4 mo, respectively). We term this predictor the androgen clock and show its “tick” is mediated by the androgen receptor and can be accelerated beyond that in normal male mice by supplementing females with dihydrotestosterone. Conversely, the removal of androgens by castration in sheep completely halted the androgen clock. In addition to potential applications in medicine and agriculture, we predict the androgen clock will prove a useful model to understand the mechanisms and processes of age-associated DNA methylation change because it can be precisely enhanced and halted using small molecule manipulation with few additional effects on the cell.